Inferior Vena Cava Filters in Trauma Patients: A National Practice Patterns Survey of U.S. Trauma Centers. Issue 12 (December 2014) - Rajasekhar, Anita; Elmariah, Hany; Lottenberg, Lawrence; Beyth, Rebecca; Lottenberg, Richard; Ang, Darwin
Inferior vena cava filters (IVCFs) for thromboprophylaxis in trauma patients are being increasingly used despite a lack of strong clinical data in support of their efficacy and conflicting clinical practice guidelines. This national survey elucidates practice patterns of IVCF use across U.S. trauma centers. A web-based survey was administered to members of the Eastern Association for the Surgery of Trauma between September 2011 and October 2011. The survey queried: 1) background and professional practice; 2) trauma patient population; 3) IVCF placement; 4) IVCF retrieval and follow-up; and 5) pharmacologic prophylaxis. Two hundred eighty-one of 1059 eligible providers completed the survey (27%). Respondents were from a wide spectrum of training backgrounds and clinical practice settings. IVCFs were used by 98.9 per cent of respondents. IVCFs in patients without known venous thromboembolism were considered by 93.2 per cent of respondents. Indications and timing of IVCF retrieval vary. Follow-up care of patients with IVCFs was not uniform. An IVCF registry was maintained by 38 per cent of trauma programs. Adjunctive pharmacologic prophylaxis was used by 96.8 per cent of respondents. This study elucidates the gaps and variations in contemporary practices of IVCF use in trauma patients. Identification of best practices in IVCF use and retrieval awaits well-designed comparative effectiveness studies.